2020
DOI: 10.3389/fpsyg.2020.01556
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link Between Mentoring and Intangible Outcomes of Entrepreneurship: The Mediating Role of Self-Efficacy and Moderating Effects of Gender

Abstract: Entrepreneurship education is increasingly becoming a focal strategy for promoting entrepreneurship, particularly to foster entrepreneurial intentions and startups. However, learning and support are equally important after startup for novice entrepreneurs to gain a good level of confidence to manage their business and achieve the desired outcomes. Using a sample of 189 young self-employed individuals in Uganda, this study examines the differential impact of mentoring and self-efficacy on the achievement of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 167 publications
0
19
0
1
Order By: Relevance
“…Moreover, we conducted interviews in a developed country where the pressure to become an entrepreneur is comparably low than in less developed countries, where entrepreneurship might be the only viable option (e.g., Baluku et al, 2019 , 2020 ). Hence, the “push” to start a business might increase for people in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we conducted interviews in a developed country where the pressure to become an entrepreneur is comparably low than in less developed countries, where entrepreneurship might be the only viable option (e.g., Baluku et al, 2019 , 2020 ). Hence, the “push” to start a business might increase for people in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with someone with low self-efficacy, a farmer with high self-efficacy is more willing to pursue and complete a task ( Elliott et al, 2020 ). The level of reported self-efficacy in one area is frequently unrelated to perceived self-efficacy in some other ( Baluku et al, 2020 ). Scholars of entrepreneurship have established the concept of “entrepreneurial self-efficacy” to concentrate on activities in the entrepreneurial domain to improve the prediction performance of self-efficacy assessments ( Neneh, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, several studies have identified mentoring as a vital factor moderating entrepreneurial students' intentions (Bosma et al. , 2012; Gimmon, 2014; Baluku et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study affirmed that the inclusion of mentoring in the educational curriculum of higher education institutions could increase entrepreneurial intentions and engender entrepreneurial activities. Also, Baluku et al. (2020) assessed the relationship between entrepreneurial mentoring and the entrepreneurial intention of students.…”
Section: Literature Reviewmentioning
confidence: 99%